Rationale and design of a stepped wedge cluster randomised trial to improve acute reperfusion treatment quality for stroke: IMPROVE stroke care in China. Issue 5 (30th March 2022) - Li, Zixiao; Wang, Chunjuan; Zhang, Xinmiao; Zong, Lixia; Zhou, Hongyu; Gu, Hongqiu; Jiang, Yong; Pan, Yuesong; Meng, Xia; Zhou, Qi; Zhao, Haifen; Yang, Xin; et al.
Abstract : Background: Reperfusion therapy is the most effective treatment for acute ischaemic stroke (AIS) but remains underutilised in China. There is an urgent need to develop tailored strategies to increase adherence to intravenous thrombolysis (IVT) and endovascular thrombectomy (EVT) within the guideline-recommended time window for eligible patients. Aims: This study aims to investigate the efficacy of a comprehensive quality improvement intervention on adherence to guideline-recommended reperfusion therapy for patients with AIS in China. Design: The Improve Acute Reperfusion Treatment Quality for Stroke in China (IMPROVE Stroke Care in China) trial is designed as a stepped wedge cluster randomised trial within 51 hospitals. We developed the comprehensive intervention 'STEP' (Strategies, Toolkit, Exploration, Paradigm) to promote the reconstruction of workflow in stroke centres and shorten in-hospital delay of reperfusion treatment for patients with AIS. The participating hospitals (clusters) were randomised to three groups (cohorts) for different predefined steps to intervention implementation. The primary outcome was the adherent rate of IVT or EVT for eligible patients within the time window. The sample size was estimated to be 7644, and was determined by the number of cases to be enrolled in five study periods to detect a relative increase of 30% (from 19% to 25%) with 90% power and intraclass correlation coefficient of 0.03. All efficacy analyses will be conducted based on the intention-to-treat principle. The primary outcome will be analysed using a mixed-effects logistic regression with a random effect for the cluster (hospital), and a fixed effect for the strategy and period. Conclusions: If the efficacy is well established, this targeted comprehensive intervention STEP will inform national strategies to increase adherence to guideline-recommended performance on reperfusion therapy. Trial registration number: clinicaltrials.gov Identifier: NCT003578107